Electroencephalography spectral edge frequency and suppression rate-guided sedation in patients with COVID-19: A randomized controlled trial - Tobar, Eduardo; Farías, José I.; Rojas, Verónica; Penna, Antonello; Egaña, José I.; Ponce, Daniela; Bravo, Daniela; Maldonado, Felipe; Gajardo, Abraham; Gutiérrez, Rodrigo (Frontiers in Medicine, 2022)
Background: Sedation in coronavirus disease 2019 (COVID-19) patients has been identified as a major challenge. We aimed to investigate whether the use of a multiparameter electroencephalogram (EEG) protocol to guide sedation in COVID-19 patients would increase the 30-day mechanical ventilation-free days (VFD). Methods: We conducted a double-blind randomized clinical trial. We included patients with severe pneumonia due to COVID-19 who required mechanical ventilation and deep sedation. We randomized to control (n=25) or BIS multiparameter group (n=25). Sedation in the intervention group was administered following the standard institutional protocols together with a flow chart designed to reduce the propofol administration dose if the EEG suppression rate was over 2% or the spectral edge frequency 95 was below 10 Hz. We performed an intention-to-treat analysis to evaluate our primary outcome (30-day VFD). Results: There was no difference in VFD at day 30 (median: 11 [IQR 0-20] days in the control group vs. 0 [IQR 0-21] days in the BIS multiparameter group, p=0.87). Among secondary outcomes, we documented a 17% reduction in the total adjusted propofol administered during the first 5 days of the protocol (median: 2.3 [IQR 1.9-2.8] mg/k/h in the control group vs. 1.9 [IQR 1.5-2.2] mg/k/h in the BMP group, p=0.005). This was accompanied by a higher average BIS value in the intervention group throughout the treatment period. Conclusion: A sedation protocol guided by multivariate EEG-derived parameters did not increase the 30-day VFD. However, the intervention led to a reduction in total propofol administration.